Spotted Fever Group and Typhus Group Rickettsioses in Humans, South Korea - Yeon-Joo Choi (Emerging Infectious Diseases, 2005)
The presence of the nucleic acid of the spotted fever group (SPG) and typhus group (TG) rickettsiae was investigated in 200 serum specimens seropositive for SFG rickettsiae by multiplex-nested polymerase chain reaction with primers derived from the rickettsial outer membrane protein B gene. The DNA of SFG, TG, or both rickettsiae was amplified in the 24 serum specimens, and sequence analysis showed Rickettsia conorii, R. japonica, and R. felis in the specimens. R. conorii and R. typhi were found in 7 serum specimens, which indicated the possibility of dual infection in these patients. These findings suggest that several kinds of rickettsial diseases, including boutonneuse fever, rickettsialpox, R. felis infection, and Japanese spotted fever, as well as scrub typhus and murine typhus, are occurring in Korea.